Optimization of Nutritional Parameters by One-Factor-At-A-Time Method for the Biosynthesis of Alkaline Protease from the Isolated Strain Alternaria alternata TUSGF1 - Polley, Tapasi; Ghosh, Uma (Current Biotechnology, 2021)
Background: Alkaline proteases are essential enzymes that have several applications in our industry. Objective: The aim was to optimized the nutritional parameters by one-factor-at-a-time (OFAT) method in solid-state fermentation. Methods: Production of protease by employing our laboratory's new isolate, Alternaria alternata TUSG1 (strain accession number- MF401426) under solid-state fermentation was optimized. The nutritional factors were investigated, and only one agricultural residue (cauliflower leaves) with different particle sizes was checked. Results: Highest enzyme production was obtained with a medium particle size of cauliflower leaves (610 U/gds) followed by coarse waste (603U/gds) and fine waste (596 U/gds) using 106 spores/ml as inoculum at 30° C for 7 days. The organism utilized carbon sources 0.5% (w/w) dextrose, fructose, maltose, sucrose, lactose, and starch. Among them, maltose was found to be the best carbon source. A variety of inorganic and organic media components were investigated for nitrogen sources of 0.3% (w/w), and skim milk was turned out to the best. Conclusion: The maximum enzyme activity was obtained with 1% of maltose, 0.5% of skim milk, and 0.05% of MgSO4. With optimized media, 1.53 fold increase in the protease production at agricultural residue cauliflower leaves was obtained.
Keywords: skim milk